(untitled) (Fiep Bulletin - online, 2014)
The health of the worker has in recent years, aroused concerns of regulatory bodies relations in the health-disease work, and are offering advice on the wearing of certain types of industrial activity, as a way to establish the load limits of the worker. The purpose of this study was to assess the burden of exposure to the heat in the manual workers of cutting sugar cane, listing the measurements with the national standards and international human. It was developed with data collected in areas planted with sugar cane in the state of Sao Paulo. The day of work in the company had run for 8 h and 30 min, where the measurements were made of the Index of Wet Bulb Globe Thermometer in, using equipment instrument Thermometer, Model pervasive Digital Globe Instrutherm mark. The survey was conducted over two days in the month of may 2007, on a rural property leased in the interior of São Paulo state, the data were collected in the month of May 2007, at the start of the cane crop in the region. This search has come to the following conclusions: the climatic conditions in the workplace were outside the range permitted by the legislation, except the period of the early day of work. The average of two days of measure of IBUTG in this period of day of work, it should be 30 minutes of work and 30 minutes of rest.